(untitled) (MAUSAM, 1966)
The Sq Tariation is derived for Alibag, Annamalainagar and Trivandrum for 1958 from retabulated hourly values of H-field according to LT (IST) for the five International Quiet Dates nearest to the local days, from the daily mean as well as from the night time level. Non-cyclic change is calculated for the same according to LT. A Fourier analysis of the Sq derived in the above manner, is performed and the results are compared with the data published in the Bombay Volumes where ,Sq and non-cyclic change is derived according to GMT. It is observed that there is considerable difference (of the order of O to 10"1) in the two estimates of the non-cyclic change but a small difference (of the order of 0 to 2.1’) in the amplitudes of the harmonic coefficients of the Sq derived in the two ways. It is concluded that Sq should preferably be derived from the local time and night time datum.